GAMBARAN PROGRAM DISEMINASI INFORMASI P4GN OLEH BNN KOTA SURABAYA - Devy Mulia Sari (JURNAL PENELITIAN KESEHATAN, 2017)
BNN is one of the institutions dealing with P4GN issues. According to East Java BNN data estimated in 2016 the number of narcotics users will increase by 2.8% or 5.8 million people. P4GN Information Dissemination Program which is a program of prevention and empowerment section aimed at target group or individual and society to gain knowledge, awareness attitude, and finally change its behavior to avoid abuse and illicit drug trafficking. The purpose of this research is to know the impact of media In the dissemination of P4GN information among the community by the prevention and empowerment section of BNN community in Surabaya City. The data obtained in the form of interviews is explanation by P2M about the dissemination program of information that runs at the time of apprenticeship. P4GN information dissemination program among the community that has a function as a tool to facilitate the public in understanding an information related to the dangers of drug abuse. In addition the media can also be a reminder about the dangers of drugs so they try to fortify itself from drug abuse